2009
DOI: 10.1002/jso.21221
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection for hepatocellular carcinoma in the elderly

Abstract: The short-term and long-term outcomes of surgery for HCC were similar in elderly and younger patients. Elderly patients with preoperative alcohol abuse should be followed closely, even after R0 surgery, because alcohol abuse is strongly correlated with postoperative recurrence and worse survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 44 publications
5
74
0
Order By: Relevance
“…Highvolume hospitals seem to be characterized by lesser morbidity and in-hospital mortality [55] . performed in the last 15 years indeed documented encouraging results [25,26,[34][35][36][37][38][39]42,[47][48][49][50] (Table 1). …”
Section: Resectionmentioning
confidence: 93%
See 2 more Smart Citations
“…Highvolume hospitals seem to be characterized by lesser morbidity and in-hospital mortality [55] . performed in the last 15 years indeed documented encouraging results [25,26,[34][35][36][37][38][39]42,[47][48][49][50] (Table 1). …”
Section: Resectionmentioning
confidence: 93%
“…With respect to the gross pathology of HCC at presentation, several studies reported that in elderly patients HCC is more frequently mono-pauci focal and it is frequently associated with less advanced fibrosis. It is well-known that multifocal liver carcinogenesis is associated with the degree of liver fibrosis while, with ageing, carcinogenesis has much more time to progress even in the absence of relevant inflammation and fibrosis [26,[34][35][36][37][38][39][40][41][42][47][48][49][50][51][52] . It has been reported that HCC in elderly patients was more frequently encapsulated [35] .…”
Section: Epidemiologic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a few reports have found that it is now possible to perform hepatectomies safely even in elderly patients who have various complications [20][21][22]. However, there have only been a few studies of perioperative liver regeneration in elderly patients who undergo hepatectomies [23].…”
Section: Discussionmentioning
confidence: 99%
“…The Child-Pugh clinical classification is used to determine the prognosis of chronic liver disease, mainly cirrhosis [2]. Slow hepatic clearance of indocyanine green (ICG) is associated with increased surgical risk and poor long-term outcomes [3]. 99m Tc-galactosyl human serum albumin is a well-established functional imaging technique for visual and quantitative analysis of radiopharmaceutical tracer uptake in the liver [4].…”
Section: Introductionmentioning
confidence: 99%